Enhanced oral bioavailability of 10-hydroxycamptothecin through the use of poly (n-butyl cyanoacrylate) nanospheres. (3rd October 2017) - Jin, Xin; Asghar, Sajid; Zhu, Xieting; Chen, Zhipeng; Liu, Junhong; Li, Yibo; Li, Hongying; Ping, Qineng; Xiao, Yanyu
Abstract: The article describes the preparation, physicochemical characterization, drug release, and in vivo behavior of 10-hydroxycamptothecin-loaded poly (n-butyl cyanoacrylate) (PBCA) nanospheres (HCPT-PBCA-NSs). HCPT-PBCA-NSs were successfully prepared via emulsion polymerization of n-butyl cyanoacrylate (BCA) monomer in acidic medium with the aid of two colloidal stabilizers (Poloxamer 188 and Dextran 70). The influence of pH, the time of polymerization, and the dosage of the drug on particle size and encapsulation efficiency (EE) were studied. HCPT-PBCA-NSs were of spherical shape and uniformly dispersed with a particle size of 135.7 nm, and zeta potential of −18.18 mV. EE, drug loading (DL), and yield of HCPT-PBCA-NSs were 51.52, 0.63, and 88.25%, respectively. FTIR, 1 H NMR, and DSC showed complete polymerization of BCA monomer and HCPT existed in the form of molecular or amorphous in NSs. In vitro release of the drug from HCPT-PBCA-NSs exhibited sustained-release behavior with an initial burst release and about 60% of HCPT was released from the formulation within 24 h of dialysis. The pharmacokinetic study in healthy rats after oral administration showed that encapsulation of HCPT into PBCA-NSs increased the Cmax about 3.84 times and increased AUC0−t about 5.40 times compared with that of HCPT suspension. It was concluded that PBCA-NSs could be a promising drug carrier to load HCPT for oral drug delivery if efforts are made in the future to improve its poor DL capacity.